2021
DOI: 10.3389/fneur.2021.646841
|View full text |Cite
|
Sign up to set email alerts
|

Dystonia Management: What to Expect From the Future? The Perspectives of Patients and Clinicians Within DystoniaNet Europe

Abstract: Improved care for people with dystonia presents a number of challenges. Major gaps in knowledge exist with regard to how to optimize the diagnostic process, how to leverage discoveries in pathophysiology into biomarkers, and how to develop an evidence base for current and novel treatments. These challenges are made greater by the realization of the wide spectrum of symptoms and difficulties faced by people with dystonia, which go well-beyond motor symptoms. A network of clinicians, scientists, and patients cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 120 publications
0
14
0
Order By: Relevance
“… 15 Prompt recognition is often limited by a lack of knowledge among medical professionals. 1 Part of the difficulty is that no reliable diagnostic test exists for dystonia, and routine brain imaging is unremarkable. In the future, kinematic, neurophysiological, and imaging tools are likely to be available to assist decisions about diagnosis.…”
Section: General Approachmentioning
confidence: 99%
See 1 more Smart Citation
“… 15 Prompt recognition is often limited by a lack of knowledge among medical professionals. 1 Part of the difficulty is that no reliable diagnostic test exists for dystonia, and routine brain imaging is unremarkable. In the future, kinematic, neurophysiological, and imaging tools are likely to be available to assist decisions about diagnosis.…”
Section: General Approachmentioning
confidence: 99%
“…It is a highly stigmatising long term condition associated with a reduced quality of life. 1 Management is a multidisciplinary partnership between general practitioners, specialists, therapists, and patients and seeks to alleviate motor and non-motor symptoms and the wider psychosocial repercussions of dystonia. This practice pointer highlights the common forms of dystonia, flags rarer causes which can have significant repercussions if not recognised, and offers a clinical roadmap for patient management.…”
mentioning
confidence: 99%
“…Because of this, many physicians may be unfamiliar with the disease and diagnosis can be challenging [ 5 ]. This may lead to delay in diagnosis and treatment, which can intensify detrimental effects of dystonia on the health-related quality of life (HRQoL) [ 6 8 ]. Previous evaluations on the quality of dystonia management found that it did not reach the required level and therefore provided several recommendations to improve dystonia-care [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Guidelines for dystonia have been developed, and the Clinical Patient Management System (CPMS), an IT platform to discuss patient cases with an expert panel, has been established. In addition, ERN-RND is closely collaborating with DystoniaNet Europe, a network with similar aims to improve dystonia-care [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ‘Dystonia Europe’ collaboration has found that healthcare professionals’ limited knowledge of dystonia is a major contributing factor to diagnostic delays [ 16 ]. One study found that only 10% of patients referred to a movement disorders clinic had been given a working diagnosis of dystonia in primary care and in approximately 1/3rd of cases, general practitioners had initially referred patients to a non-neurologist [ 17 ].…”
Section: Introductionmentioning
confidence: 99%